Medium-and low-voltage planning of electric power distribution systems with distributed generation, energy storage sources, and electric vehicles - Rupolo, Diogo [UNESP]; Mantovani, José Roberto Sanches [UNESP]; Pereira, Benvindo Rodrigues (Institute of Electrical and Electronics Engineers (IEEE), 2019)
In this paper, medium- and low-voltage planning of electric power distribution systems with distributed generation (DG), energy storage sources (ESS) allocation and electric vehicles (EV) is carried out. In the planning, DG is owned by independent producers and ESS as owned by distribution companies (DISCO). Due to the uncertainties associated with demand and renewable energy sources, a methodology for scenarios generating based on annual historical data of demand, wind speed, and solar irradiation is used. As the developed model has high computational complexity, we use a General Variable Neighborhood Search metaheuristic (GVNS), along with the Chu-Beasley Genetic Algorithm (CBGA) to find solutions. In order to show the efficiency and robustness of the planning algorithm, several tests are performed in an integrated system with 24 bus in medium voltage (MV) and 172 bus in low voltage (LV).
Keywords: Distributed Generation; Electric Vehicles; Energy Storage Sources; General Variable Neighborhood Search; Integrated Systems Planning